A dinâmica da traumatologia na clínica psicanalítica: os cavaleiros de tânatos - Souza, Palmira Catarina Aguiar de (2024)
The present psychoanalytic research, by taking the Hungarian psychoanalyst Sándor Ferenczi as its base author, brings metapsychological constructions on the traumatological dynamics in cases of patients who have suffered abuse, and can, in this way, contribute to current psychoanalytic clinical practice. Ferenczi studied the traumatic process in a dynamic way, promoting a new perspective on the understanding of psychic phenomena, particularly in patients considered borderline cases. The present study focuses on the researcher's experience, based on some clinical vignettes, allowing us to describe the male patient abused in childhood and the way he deals with the trauma, making him a knight of thanatos, a metaphor used to describe a type of patient which predominates in this researcher's career as a psychoanalyst. Thanatos knights concern a type of patient who has complex and similar psychic characteristics to borderline cases. In this sense, Ferenczi's theoretical basis allowed us to present a contemporary way of treating borderline patients in an elastic way